Antioxidant conductive heat dissipation copper paste adhesive and preparation method thereof
By using a combination of reactive monomer, thermally curing resin, polymerization inhibitor and conductive copper powder in the grain adhesive, an antioxidant conductive heat dissipation copper paste adhesive was prepared, and the lack of conductivity and heat dissipation in the prior art was solved. The problem of efficient conductivity and thermal conductivity is achieved, and the cost and environmental impact is reduced.
Patent Information
- Application Number
- CN202310771850.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-28
- Publication Date
- 2024-12-31
AI Technical Summary
The existing grain adhesives do not perform well in terms of electrical conductivity and heat dissipation, and the fine metal particles used such as silver powder are expensive and unstable, affect the environment, and have poor coating properties.
Develop an antioxidant conductive heat dissipation copper slurry adhesive, including reactive monomers, thermal curing resins, polymerization inhibitors, conductive copper powder and thixotropic agents, and is prepared by vacuum defoaming step. The median particle size of conductive copper powder is mixed. At 0.1-10μm, D90/D50 is less than 3, thereby improving electrical conductivity and thermal conductivity.
The hardened antioxidant conductive heat dissipation copper paste adhesive has good adhesion, high conductivity, high thermal conductivity and thermal mechanical properties, providing low and long-term stable contact resistance without the need for additional starting agent, cost Low and stable.
Smart Images

Figure HDA0004308127980000011 
Figure HDA0004308127980000021 
Figure HDA0004308127980000022
Abstract
Description
Technical Field
[0001] The invention relates to an anti-oxidation conductive heat dissipation copper paste adhesive and a preparation method thereof, so as to obtain an anti-oxidation conductive heat dissipation copper paste adhesive for grain adhesion. Background Art
[0002] Die adhesive is used to bond the die to the lead frame, substrate, circuit package or printed wiring board. The die adhesive should have good adhesion and mechanical strength, and also need to have good thermal conductivity to effectively remove the heat generated by the die. In the semiconductor industry, fine metal particles such as silver, copper, and nickel are dispersed in a curable resin composition to prepare a conductive paste or thermal paste. Such conductive paste or thermal paste is cured by heat treatment to form a conductive medium or a thermally conductive medium. Currently, conductive paste or thermally conductive paste containing fine metal particles can be used to form conductive circuits on printed circuit boards, to form electrodes for electronic parts or solar cells, to form conductive films for electromagnetic wave shielding covers, or to bond or adhere chip parts such as capacitors, resistors, diodes, memory, and operating components to substrates, etc.
[0003] Please refer to CN113004844A, which discloses a high heat dissipation conductive adhesive including epoxy resin, flaky silver powder and new type of silver powder. However, the conductive particles used are silver particles, and the particle size of the silver particles is between 2-20μm. This particle size will result in poor filling space utilization, conductivity and heat dissipation of metal particles in the conductive colloid.
[0004] Please also refer to CN108102578A, which discloses a method for preparing a conductive adhesive. The components of the conductive adhesive include epoxy resin, silver powder, curing agent, leveling agent, etc., wherein the metal particle content is controlled at 75-80%. However, a lower proportion of metal particles will affect the conductivity of the conductive adhesive.
[0005] Furthermore, the metals used in the conductive paste or thermal conductive paste containing metal fine particles are, for example, silver powder disclosed in Taiwan Patent No. TWI632114(B), or silver-plated copper sheet disclosed in Taiwan Patent No. TW I453762(B), or solder powder disclosed in Taiwan Publication No. TW 201016652(A); however, silver metal is expensive, tin metal is easy to change and has high instability, and there is also concern about environmental pollution, and the conductive paste or thermal conductive paste made of copper-plated silver has poor coating properties, so the development of stable and low-cost conductive paste or thermal conductive paste is an important research and development theme. Summary of the invention
[0006] At present, the inventors have found that the existing die adhesives still have some shortcomings in practical use, so they have been working tirelessly and using their rich professional knowledge and many years of practical experience to improve them, and have developed the present invention accordingly.
[0007] The invention relates to an anti-oxidation conductive heat dissipation copper paste adhesive and a preparation method thereof. The anti-oxidation conductive heat dissipation copper paste adhesive comprises a reactive monomer, a thermosetting resin, an inhibitor, a conductive filler and a thixotropic agent.
[0008] The present invention also relates to a method for preparing an antioxidant conductive heat dissipation copper paste adhesive, comprising mixing a reactive monomer, a thermosetting resin and an inhibitor to obtain a first mixed copolymer; adding a conductive filler to the first mixed copolymer and mixing them to obtain a second mixed copolymer; and adding a thixotropic agent to the second mixed copolymer, mixing them to obtain a vacuum degassing step to obtain an antioxidant conductive heat dissipation copper paste adhesive.
[0009] In one embodiment of the present invention, the reactive monomer includes at least one of triethoxy trimethylolpropane triacrylate (Ethoxylated Trimethylolpropane Triacrylate), rimethylolpropane ethoxylate triacrylate, 1,6-hexanediol diacrylate (Hexamethylene diacrylate), isobornyl acrylate or tripropylene glycol diacrylate.
[0010] In one embodiment of the present invention, the thermosetting resin includes polyurethane acrylate or acrylic ester or acrylate, and the polymerization inhibitor includes 4-tert-Butylcatechol or Duomeen TDO.
[0011] In one embodiment of the present invention, the conductive filler is conductive copper powder.
[0012] In one embodiment of the present invention, the median particle size (D50) of the conductive copper powder is between 0.1 μm and 10 μm, and the D90 / D50 of the particle size of the conductive copper powder is less than 3.
[0013] In one embodiment of the present invention, the oxidation-resistant conductive heat-dissipating copper paste adhesive comprises 3-17 wt % of reactive monomer, 5-15 wt % of thermosetting resin, 0.5-4 wt % of polymerization inhibitor, 0.1-3 wt % of thixotropic agent, and 75-90 wt % of conductive filler.
[0014] The antioxidant conductive heat dissipation copper paste adhesive of the present invention can be hardened (cured) within a temperature range of 150-250° C., and the required hardening (curing) time is about 20-120 minutes. The hardened (cured) product has good adhesion, high electrical conductivity, high thermal conductivity and improved thermal mechanical or mechanical fatigue resistance; and the antioxidant conductive heat dissipation copper paste adhesive after hardening (curing) can make the components connected on both sides conductively interconnected, wherein the interconnection can show low and long-term stable contact resistance and provide good high thermal conductivity; in addition, the conductive copper powder used in the present invention has the effect of a catalyst and an initiator, so there is no need to add an initiator to achieve the same effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a scanning electron microscope photo of the antioxidant conductive heat dissipation copper paste adhesive of the present invention;
[0016] Figure 2 This is a photo of the anti-oxidation conductive heat dissipation copper paste adhesive of the present invention after the conductive heat dissipation copper paste has been left to stand for many days;
[0017] Figure 3 This is a crystal pushing analysis diagram of the conductive heat dissipation copper paste of the present invention and the commercially available grain adhesive;
[0018] Figure 4A This is a thickness observation photograph of a semiconductor component encapsulated with the antioxidant conductive heat dissipation copper paste adhesive of the present invention and after thermal curing;
[0019] Figure 4B This is a photo of chip creep height observation after the semiconductor component is encapsulated with the anti-oxidation conductive heat dissipation copper paste adhesive of the present invention and thermally cured;
[0020] Figure 5 The present invention is a scanning electron microscope slice photograph of the antioxidant conductive heat dissipation copper paste adhesive contained in the thermally cured conductive heat dissipation copper paste of the present invention to encapsulate a semiconductor component. DETAILED DESCRIPTION
[0021] In order to make the effects of the technical means of the present invention more complete and clear, the following detailed description is given, and please refer to the disclosed drawings. The following specific embodiments can further prove the practical application scope of the present invention, but are not intended to limit the scope of the present invention in any form.
[0022] The invention relates to an anti-oxidation conductive heat dissipation copper paste adhesive and a preparation method thereof. The anti-oxidation conductive heat dissipation copper paste adhesive mainly comprises a reactive monomer, a thermosetting resin, an inhibitor, a conductive filler and a thixotropic agent.
[0023] The preparation method of the antioxidant conductive heat dissipation copper paste adhesive of the present invention comprises:
[0024] Step 1: Mix a reactive monomer, a thermosetting resin and a polymerization inhibitor, and stir them uniformly at high speed using a degassing mixer to obtain a first mixed copolymer;
[0025] Step 2: adding a conductive filler into the first mixed copolymer, and stirring evenly with a degassing mixer at high speed to obtain a second mixed copolymer; and
[0026] Step 3: Add a thixotropic agent into the second mixed copolymer, stir with a vacuum degassing machine, perform vacuum degassing and mix evenly to obtain the antioxidant conductive heat dissipation copper paste adhesive of the present invention.
[0027] In addition, the reactive monomer includes triethoxylatedtrimethylolpropane triacrylate, trimethylolpropane ethoxylate triacrylate, hexamethylene diacrylate, isobornyl acrylate or tripropylene glycol diacrylate; the weight percentage of the reactive monomer is preferably 3-17 weight percentage of the total antioxidant conductive heat dissipation copper paste adhesive. The reactive monomer acts as a reactive diluent and reacts with the thermosetting resin to become a part of the hardened material due to the epoxy group in its molecule. Therefore, the antioxidant conductive heat dissipation copper paste adhesive of the present invention does not have the problem of diluent volatilization (dry out). In addition, when such reactive monomers are used, the glass transition temperature (Tg) or toughness of the hardened product can be reduced.
[0028] The thermosetting resin used in the present invention may be a monomer, oligomer or prepolymer made of a natural or synthetic, modified or unmodified resin; wherein the resin is not completely hardened and / or cross-linked, and therefore can be further hardened and / or cross-linked by polymerization, polycondensation and / or polyaddition reaction; the thermosetting resin may be in liquid form at room temperature or at a relatively low temperature (e.g., below 100°C). In addition, the above-mentioned "hardening" and "cross-linking" refer to the reaction of making the thermosetting resin and / or the thermosetting resin react with the reactive monomer to produce a cross-linked or cured structure; the thermosetting resin of the present invention includes polyurethane acrylate (PUA) or acrylic ester acrylate. The weight percentage of the thermosetting resin in the antioxidant conductive heat dissipation copper paste adhesive of the present invention is preferably 5-15% by weight relative to the total weight of the antioxidant conductive heat dissipation copper paste adhesive.
[0029] The polymerization inhibitor used in the present invention comprises 4-tert-Butylcatechol or Duomeen TDO, and the weight percentage of the inhibitor is preferably 0.5-4 weight percentage in the antioxidant conductive heat dissipation copper paste adhesive.
[0030] The thixotropic agent used in the present invention includes polyamide wax or oxidized polyethylene wax, and the content of the thixotropic agent is preferably 0.1-3 weight percent of the total antioxidant conductive heat dissipation copper paste adhesive.
[0031] In the anti-oxidation conductive heat dissipation copper paste adhesive of the present invention, the conductive filler is a conductive copper powder, and its weight percentage is preferably 65 weight percent of the weight of the anti-oxidation conductive heat dissipation copper paste adhesive, more preferably 70 weight percent or more, more preferably 76 weight percent or more, and more preferably 82 weight percent or more. However, its weight percentage is preferably less than 90 weight percent of the weight of the anti-oxidation conductive heat dissipation copper paste adhesive, more preferably less than 87 weight percent, and more preferably less than 84 weight percent, so that the grain bonding layer formed after the anti-oxidation conductive heat dissipation copper paste adhesive of the present invention is hardened has better conductivity. And a high weight percentage of the filled conductive filler can improve the heat dissipation of the anti-oxidation conductive adhesive. The preferred weight percentage of the above conductive filler will make the viscosity of the obtained anti-oxidation conductive heat dissipation copper paste adhesive moderate, and the operability (operability) during dispensing or spraying is optimized.
[0032] In addition, the median particle size of the conductive copper powder used in the present invention (also known as the particle size at 50% cumulative, D50) is preferably 0.5-10μm, more preferably 1.0-7.0μm, and even more preferably 2.0μm-4.0μm; this means that in the conductive filler, the particle size of 50vol% of the conductive filler is preferably between 0.5-10μm, preferably between 1.0-7μm, and even more preferably between 2.0-4.0μm. And the particle size (D90) at the cumulative 90% in the volume-based particle size distribution of the conductive filler added to the die adhesive of the present invention is preferably between 1.8-9μm, preferably 3.0-9μm, and even more preferably 3-5.5μm, please refer to Figure 1 The scanning electron microscope photo shows that the conductive copper powder appears as white or gray particles that are evenly dispersed and do not aggregate into clumps.
[0033] Conductive copper powder with a smaller particle size can reduce the gap between the conductive fillers after the anti-oxidation conductive heat dissipation copper paste adhesive of the present invention is hardened, and also make the anti-oxidation conductive heat dissipation copper paste adhesive of the present invention have a high storage stability, and it is not easy to cause the conductive filler to precipitate during storage. In addition, when the particle size distribution of the conductive filler is obvious, after mixing with the thermosetting resin, the conductive filler can be gathered more densely, and the contact area of the conductive filler is wider, thereby improving the electrical conductivity and thermal conductivity of the die adhesive.
[0034] In addition, when preparing the antioxidant conductive heat dissipation copper paste adhesive of the present invention, the width of the particle size distribution of the conductive filler used is preferably narrower. For example, when the ratio of the cumulative 90% particle size (D90) in the volume-based particle size distribution of the conductive filler to the cumulative 50% particle size (D50) in the particle size distribution (D90 / D50) is 3.0 or less, the prepared antioxidant conductive heat dissipation copper paste adhesive has better efficacy, and the D90 / D50 of the conductive filler is preferably less than 2.3, and the optimal D90 / D50 ratio of the conductive filler is less than 1.7. That is, by adjusting the ratio of D90 to D50 (D90 / D50) of the conductive filler, the dispersibility of the conductive filler in the antioxidant conductive heat dissipation copper paste adhesive of the present invention can be improved, thereby improving the reliability of the antioxidant conductive heat dissipation copper paste adhesive of the present invention. The ratio of the conductive filler D90 to D50 used in the present invention is quite low, so the physical stability of the prepared anti-oxidation conductive heat dissipation copper paste adhesive during storage is quite high and precipitation is not likely to occur. Figure 2 , which are observation photos of the antioxidant conductive heat dissipation copper paste adhesive of the present invention after being placed and observed for more than 30 days, no precipitation phenomenon occurs, that is, the antioxidant conductive heat dissipation copper paste adhesive of the present invention has the advantage of not being easy to precipitate.
[0035] In addition, the anti-oxidation conductive heat dissipation copper paste adhesive of the present invention has a lower hardening shrinkage rate in the interface, and also inhibits the increase of the interface stress, and increases the interface strength of the die adhesive, thereby improving the die shear value, see Figure 3 , which is a comparison of the crystal pushing values of the antioxidant conductive heat dissipation copper paste adhesive of the present invention and the commercially available grain adhesive. The crystal pushing value of the antioxidant conductive heat dissipation copper paste adhesive of the present invention is increased by 150-200% compared with the commercially available crystal pushing value.
[0036] The anti-oxidation conductive heat dissipation copper paste adhesive prepared by the invention comprises 3-17wt% of reactive monomer, 5-15wt% of thermosetting resin, 0.5-4wt% of polymerization inhibitor, 75-90wt% of conductive copper powder and 0.1-3wt% of thixotropic agent.
[0037] The anti-oxidation conductive heat dissipation copper paste adhesive prepared by the present invention can be used for the adhesion of grains, that is, to form a hardened grain bonding layer between the semiconductor component and the substrate so as to mount the semiconductor component on the substrate; the grain bonding layer after the anti-oxidation conductive heat dissipation copper paste adhesive of the present invention is hardened is more reliable and has the advantage of low cost compared with the conventional grain adhesives.
[0038] In addition, when the antioxidant conductive heat dissipation copper paste adhesive of the present invention is used, it is first applied to the substrate by a dispensing method or a spraying method, and then a semiconductor component is mounted on the die adhesive to fix the semiconductor component; when used, the antioxidant conductive heat dissipation copper paste adhesive of the present invention can cover the side of the semiconductor component, so the present invention has the functions of fixing the semiconductor component and covering the semiconductor component at the same time, and the semiconductor packaging is performed with the antioxidant conductive heat dissipation copper paste adhesive of the present invention, and the packaging glue creeping height can be controlled to be 50-80% of the thickness of the semiconductor component, or even to 30-50%, and it does not affect the working performance of the semiconductor component, so as to avoid the antioxidant conductive heat dissipation copper paste adhesive from creeping too high, resulting in a short circuit of the semiconductor component, Figure 4A A photograph of the thickness of a longitudinal section of a semiconductor component observed by an electron microscope after the semiconductor component is encapsulated using the anti-oxidation conductive heat dissipation copper paste adhesive of the present invention, and Figure 4B This is an electron microscope observation photo of the chip glue creeping height observed from a top view angle after the semiconductor component is encapsulated using the anti-oxidation conductive heat dissipation copper paste adhesive of the present invention. Figure 4A and Figure 4B The observation results show that the antioxidant conductive heat dissipation copper paste adhesive of the present invention has no excessive adhesive creeping phenomenon.
[0039] The anti-oxidation conductive heat dissipation copper paste adhesive prepared by the present invention has a density between 3.0 and 4.7 g / cc, so it is possible to prevent the occurrence of an uneven state in the conductive filler in the grain bonding layer formed after the anti-oxidation conductive heat dissipation copper paste adhesive is hardened.
[0040] In addition, the antioxidant conductive heat dissipation copper paste adhesive prepared by the present invention is measured using a Brookfield cone / plate viscometer with a rotor type of CP-51, and its viscosity at a rotation rate of 0.5 rpm and 5 rpm is measured. Under the test conditions of 25° C. and 5.0 rpm, its viscosity is 6,000-50,000 CP, TI (0.5 / 5) = 1.3-6, and has the appropriate rheological range, viscosity, and physical stability during storage.
[0041] In addition, the anti-oxidation conductive heat dissipation copper paste adhesive prepared by the present invention has a volume resistivity between 10 -3 Ohm-cm to 10 -5 Ohm-cm; wherein the volume resistivity is measured by applying a 4×4 square centimeter, 5-100 micrometer (μm) thick anti-oxidation conductive heat dissipation copper paste adhesive on a glass slide by screen printing, and curing it in a nitrogen oven. The curing conditions are to heat the film from 25°C to 130°C in 40 minutes, and keep it at 130°C for 30 minutes, then heat it from 130°C to 220°C over 30 minutes, and finally keep it at 220°C for 60 minutes. After curing, the resistance is measured by a four-point probe, and the volume resistivity is calculated by the formula.
[0042] The anti-oxidation conductive heat dissipation copper paste adhesive of the present invention can be used to cover an area of up to 5×5 mm 2The die is adhered to the substrate. The material on the back of the die can be silicon crystal or a metal coating, such as gold coating, silver coating, copper coating or aluminum coating. Then, different curing processes are used to cure the anti-oxidation conductive heat dissipation copper paste adhesive so that there is no gap between the die and the substrate. In order to meet the needs of users, the curing process can be but not limited to the following three curing processes: the first curing process: the temperature is raised from room temperature to 130°C in 40 minutes, and the temperature is maintained at 130°C for 30 minutes, and then the temperature is raised from 130°C to 220°C in 30 minutes, and the temperature is maintained at 220°C for 60 minutes; or the second curing process: the temperature is raised from room temperature to 130°C in 20 minutes. The room temperature is raised to 120°C and maintained at 120°C for 10 minutes, then the temperature is raised from 120°C to 200°C in 20 minutes and maintained at 200°C for 60 minutes, or the third curing process is: the temperature is raised from room temperature to 180°C in 40 minutes and maintained at 180°C for 90 minutes; when the above three curing processes are carried out, no additional pressure is required to successfully cure the antioxidant conductive heat dissipation copper paste adhesive of the present invention; when the antioxidant conductive heat dissipation copper paste adhesive of the present invention is used to adhere the back material of silicon crystal or a layer of metal coating grain to a general or surface roughened pre-electroplating copper frame (Pre-Plating Frame), the above curing process is used to cure the antioxidant conductive heat dissipation copper paste adhesive to form a hardened layer, the thermal conductivity of which is 3-20W / mk, and the lower limit of the die shear strength at room temperature is 2200g / (1mm 2 )above.
[0043] In addition, after the anti-oxidation conductive heat dissipation copper paste adhesive of the present invention is used to encapsulate the die, the encapsulated die is placed at a temperature of 85°C and a humidity of 85% for 168 hours to absorb moisture, and a temperature cycling test is performed at a temperature range of -65°C to 150°C. After 4000 temperature cycles, the test is performed using a scanning acoustic tomography. It is found that there is no delamination between the solidified layer formed by the anti-oxidation conductive heat dissipation copper paste adhesive of the present invention and the frame and the die, indicating that the solidified layer formed by the anti-oxidation conductive heat dissipation copper paste adhesive of the present invention has a certain internal stress and can suppress the warping caused by moisture absorption or temperature changes.
[0044] The application scope of the anti-oxidation conductive heat dissipation copper paste adhesive of the present invention includes but is not limited to Quad Flat Non-leaded Package (QFN), Quad Flat Package (QFP), Small Outline Package (SOP), Chip Size Package (CSP), Small Outline Non-leaded Package (SON), Ball Grid Array (BGA), Lead Flame BGA (LF-BGA), Flip Chip BGA (FCBGA) or Molded Array Process BGA (MAPBGA), etc.
[0045] The antioxidant conductive heat dissipation copper paste adhesive of the present invention has a unique adhesive property due to its unique formula. When it is dispensed on a surface roughened frame operating machine by high-speed needle dispensing / spraying operation, it has good recognition by automated optical inspection, so it can achieve a more accurate die bonding (die bond) effect, solving the problem that when the existing die adhesive is applied to the surface roughened frame, the machine recognition is poor and the die cannot be accurately aligned. In addition, the antioxidant conductive heat dissipation copper paste adhesive of the present invention can not dry for more than 140 hours when using the high-speed needle dispensing / spraying operation method, and also solves the problem that the existing die bonding adhesive is easy to dry under the high-speed needle dispensing / spraying operation. Therefore, the antioxidant conductive heat dissipation copper paste adhesive of the present invention can optimize the production workability.
[0046] The following provides practical implementations of the present invention, which can further demonstrate the practical application scope of the present invention, but are not intended to limit the scope of the present invention in any form.
[0047] The antioxidant conductive heat dissipation copper paste adhesive in the following embodiments comprises 6-10wt% of reactive monomers, 8-13wt% of acrylic ester acrylate, 0.8-1.5wt% of 4-tert-Butylcatechol, 0.6-1.6wt% of polyamide wax, and 73.8-84.5wt% of conductive copper powder, wherein the reactive monomer comprises at least one of tripropylene glycol diacrylate or trimethylolpropane ethoxylate triacrylate, and wherein the conductive copper powder is a spherical powder with a particle size D50 between 0.1-10μm.
[0048] In addition, the morphology of the conductive copper powder in the anti-oxidation conductive heat dissipation copper paste adhesive of this embodiment was observed by a scanning electron microscope (SEM). Figure 5 (A) and Figure 5 In (B), the scanning electron microscope slice photograph after the semiconductor component is encapsulated and cured using the antioxidant conductive heat dissipation copper paste adhesive of the present invention can be observed that the conductive copper powder in the antioxidant conductive heat dissipation copper paste adhesive is a spherical structure. This structure can make the conductive copper powder more compact during the curing (hardening) process of the antioxidant conductive heat dissipation copper paste adhesive of the present invention, and can prevent the grain adhesive from clogging the needle used for dispensing during the dispensing or spraying operation, so that the dispensing or spraying operation is smoother.
[0049] Then the above-prepared anti-oxidation conductive heat dissipation copper paste adhesive was applied to die fixation and tested:
[0050] Embodiment 1
[0051] The above-prepared anti-oxidation conductive heat dissipation copper paste adhesive was applied to a die bonding machine (ASM AD 838) by dispensing, with a nozzle size of 0.2-0.4 mm, a squeeze time of 20-60 ms, a squeeze pressure of 90-110 KPa, and a squeeze vacuum value of 1. Vacuum) between -8 and -11 KPa, and attach it to a general or surface roughened pre-plated copper frame with a length of 3.5 mm, a width of 2.5 mm and a thickness of 0.65 mm; then, a silicon chip with a length of 0.955 mm, a width of 0.875 mm and a thickness of 0.2 mm is arranged on the above-mentioned anti-oxidation conductive heat dissipation copper paste adhesive to obtain a die adhesion layer with a thickness of 5 μm-30 μm; the die adhesion layer is cured, and the curing process is to increase the temperature from 25° C. to 130° C. within 40 minutes, and then keep the temperature at 130° C. for 10 minutes, then increase the temperature from 130° C. to 200° C. within 30 minutes, and finally keep the temperature at 200° C. for 1 hour to obtain a cured layer; then, encapsulate it with an epoxy molding compound for semiconductor sealing; the package size in this embodiment is 3.5 mm in length, 2.5 mm in width and 0.85 mm in thickness; finally, post mold curing is performed The invention also provides a method for obtaining a semiconductor device of a quad flat no-lead package (QFN). The test results show that the antioxidant conductive heat dissipation copper paste adhesive of the present invention can pass the tests of moisture sensitivity levels MSL1, MSL2 and MSL3.
[0052] In addition, the package structure prepared by using the roughened surface pre-electroplated copper frame and silicon chip and the antioxidant conductive heat dissipation copper paste adhesive has a lower limit of die shear strength of 2200 g / (1 mm×1 mm) or more at 25°C, indicating that the antioxidant conductive heat dissipation copper paste adhesive of the present invention has a certain adhesion to support the external force caused in the subsequent processing process.
[0053] In this embodiment, 500 semiconductor packaging devices were manufactured by the above method and the following tests were performed. First, the semiconductor packaging devices were placed in an environment with a temperature of 85°C and a humidity of 85% for 168 hours. Then, the semiconductor packaging devices were subjected to a temperature cycling test, in which the semiconductor packaging devices were placed in an environment with a temperature cycle of -65°C to 150°C for 4000 cycles. Finally, the semiconductor packaging devices were tested by scanning acoustic tomography.
[0054] The test results show that in the semiconductor device treated under the above conditions, there is no delamination between the solidified body formed by the antioxidant conductive heat dissipation copper paste adhesive of the present invention and the copper frame or silicon chip with a roughened surface, indicating that the antioxidant conductive copper paste adhesive prepared by the present invention has a certain internal stress and can also suppress the warping caused by moisture absorption or temperature changes.
[0055] Embodiment 2
[0056] The above-prepared anti-oxidation conductive heat dissipation copper paste adhesive is attached to a surface roughened copper frame with a length of 8.5 mm, a width of 3.4 mm and a thickness of 0.15 mm by dispensing, and then a silicon chip with a length of 4.275 mm, a width of 2.525 mm, a thickness of 0.2 mm and a metal coating on the back of the chip is arranged on the anti-oxidation conductive heat dissipation copper paste adhesive to obtain a die adhesion layer with a thickness of 10 μm to 35 μm; then a curing process is performed, the curing process is to heat the die adhesion layer from room temperature to 120° C. in 20 minutes, keep the temperature at 120° C. for 10 minutes, and then heat the temperature from 120° C. to 200° C. in 20 minutes, and keep the temperature at 200° C. for 60 minutes to obtain a cured layer; then, the semiconductor sealing epoxy molding compound is used for packaging, and the size of the package is 3.5 mm in length, 2.5 mm in width and 0.85 mm in thickness; finally, post mold curing is performed. cure) step to obtain a semiconductor device of small outline package (SOP); the test results show that the antioxidant conductive heat dissipation copper paste adhesive of the present invention can pass the tests of moisture sensitivity levels MSL1, MSL2 and MSL3.
[0057] In addition, the package structure prepared by using the roughened surface pre-electroplated copper frame and silicon chip and the antioxidant conductive heat dissipation copper paste adhesive has a lower limit of die shear strength of 2500 g / (1 mm×1 mm) or more at 25°C, indicating that the antioxidant conductive heat dissipation copper paste adhesive of the present invention has a certain adhesion to support the external force caused in the subsequent processing process.
[0058] In addition, 500 of the above-mentioned semiconductor devices were manufactured using the above-mentioned method, and the following tests were performed: the above-mentioned semiconductor devices were placed in an environment with a temperature of 85°C and a humidity of 85% for 168 hours; then, these semiconductor packaging devices were subjected to a temperature cycle test, in which these semiconductor packaging devices were placed in an environment with a temperature cycle of -65°C-150°C, and after 4000 cycles, they were inspected using an ultrasonic scanning microscope.
[0059] The test results show that in these semiconductor devices, there is no delamination between the cured layer formed by the antioxidant conductive heat dissipation copper paste adhesive of the present invention and the above-mentioned surface roughened copper frame or the above-mentioned silicon chip, indicating that the antioxidant conductive heat dissipation copper paste adhesive of the present invention has a certain internal stress and can also suppress the warping caused by moisture absorption or temperature changes.
[0060] Embodiment 3
[0061] In this embodiment, a die bonding machine (ASM AD 838) is used to dispense the anti-oxidation conductive heat dissipation copper paste adhesive of the present invention, with a nozzle size of 0.2-0.3 mm, a squeeze time of 20 ms to 60 ms, and a squeeze pressure of 1.5 g. The method comprises the following steps: attaching the pre-plated copper frame to a general or surface roughened copper frame with a length of 9.9 mm, a width of 3.9 mm and a thickness of 1 mm under the condition of a pressure of 120 KPa to 160 KPa and a squeeze vacuum value of -4 KPa to -6 KPa, and then placing a silicon chip with a length of 1.935 mm, a width of 1.01 mm and a thickness of 0.2 mm on an anti-oxidation conductive heat dissipation copper paste adhesive to form a grain layer adhesive layer with a thickness of 5 μm to 30 μm; then performing a curing process, wherein the curing process conditions are to raise the temperature from room temperature to 180°C in 40 minutes and to maintain the temperature at 180°C for 90 minutes to form a cured layer; then, using an epoxy molding mold for semiconductor sealing (Epoxy Molding Compound) is packaged, and the package size is 9.9 mm in length, 3.9 mm in width and 1.65 mm in thickness; finally, post-mold curing is performed to obtain a semiconductor device of a small outline no-lead package (SON). The test results show that the antioxidant conductive heat dissipation copper paste adhesive of the present invention can pass the tests of moisture sensitivity levels MSL1, MSL2 and MSL3.
[0062] The lower limit of the die-cutting strength of the antioxidant conductive heat-dissipating copper paste adhesive of the present invention, the pre-electroplating copper frame and the silicon chip at 25°C is 2300g / (1mm×1mm) or more, indicating that the antioxidant conductive heat-dissipating copper paste adhesive of the present invention has a certain adhesion to support the external force caused in the subsequent processing process; and 100 semiconductor devices of the third embodiment were manufactured by the above method, and the following tests were performed: after the semiconductor devices were placed at a temperature of 85°C and a humidity of 85% for 168 hours, the semiconductor devices were subjected to a temperature cycle test at a temperature range of -65°C-150°C, and the number of temperature cycles was 4000 times; finally, an ultrasonic scanning microscope was used for detection, and the test results showed that the solidified layer formed by the antioxidant conductive heat-dissipating copper paste adhesive of the present invention and the pre-electroplating copper frame or the silicon chip did not delaminate, indicating that the solidified layer formed by the antioxidant conductive heat-dissipating copper paste adhesive of the present invention has a certain internal stress and can also suppress the warping caused by moisture absorption or temperature changes.
[0063] In addition, the above-prepared anti-oxidation conductive heat dissipation copper paste adhesive was analyzed by a dynamic mechanical analyzer (DMA), a thermomechanical analyzer (TMA), a thermogravimetric analyzer (TGA), and a differential scanning calorimeter (DSC). Before the analysis, the anti-oxidation conductive heat dissipation copper paste adhesive of the present invention was poured onto a Teflon mold, heated in a vacuum oven overnight, and placed in a vacuum high-temperature furnace for curing the next day. After cooling to obtain a thin film, the thin mold was removed for analysis as follows:
[0064] (1) Dynamic Mechanical Analyzer Analysis
[0065] The instrument model used is TA-Q800. The film obtained above is clamped on the fixture on the machine table in the heating furnace, nitrogen is introduced, and the heating rate is set to 5℃ per minute, from -50℃ to 350℃. The film is recorded under the temperature, force and frequency, etc., to observe its strength, viscosity, elasticity and phase transition characteristics. The measured loss factor (Tanδ) is 45-70℃, and its storage modulus (Storage Modulus, E') is 5500-9500MPa at 25℃ and 400-1200MPa at 200℃.
[0066] (II) Thermomechanical Analyzer Analysis
[0067] The instrument model used is TA-Q400. The film is clamped in a thermal expansion fixture and placed in a heating furnace. Nitrogen (~120 mL / min) is introduced, and the heating rate is set to 10°C per minute. The temperature is raised from -50°C to 250°C, and the shape change of the sample under temperature change is recorded. The glass transition temperature (Tg) of the film is 53-60°C, the Alpha 1 value of the coefficient of thermal expansion (CTE) is 35-60ppm / °C, and the Alpha 2 value is 120-150ppm / °C.
[0068] (III) Thermogravimetric analysis
[0069] The instrument model used is TA-Q50. The above film is placed on a platinum plate and then placed in a heating furnace. A fixed ratio of nitrogen / air mixed gas is introduced. The heating rate is set to 10°C per minute, and the temperature is raised from 30°C to 350°C. The change in sample weight with temperature and time is recorded to obtain the thermal stability (Thermal stability weight) of the film. The measurement results show that the antioxidant conductive heat dissipation copper paste adhesive of the present invention has good thermal stability, and only a thermogravimetric loss of 5-6% is achieved when the temperature is raised to 350°C.
[0070] (IV) Moisture Sensitivity Level (MSL) Test
[0071] This test is performed according to JEDEC standard J-STD-20, and the measurement conditions are MSL1, maintaining the sample at 85°C and 85% relative humidity for 168 hours; MSL2, maintaining the sample at 85°C and 60% relative humidity for 168 hours; and MSL3, maintaining the sample at 30°C and 60% relative humidity for 192 hours. The test results show that the anti-oxidation conductive heat dissipation copper paste adhesive of the present invention can pass the tests of MSL1, MSL2 and MSL3.
[0072] The conductive filler in the antioxidant conductive heat dissipating copper paste adhesive of the present invention, especially the conductive copper powder, has the effects of a catalyst and an initiator at the same time, so there is no need to add an initiator to the composition to achieve the same effect.
[0073] In addition, the oxidation-resistant conductive heat-dissipating copper paste adhesive of the present invention has good adhesion, high electrical conductivity, high thermal conductivity and improved resistance to thermal mechanical or mechanical fatigue, and can make the components connected on both sides of the adhesive conductively interconnected, exhibit low and long-term stable contact resistance, and provide good high thermal conductivity.
Claims
1. An anti-oxidation conductive heat dissipation copper paste adhesive, comprising a reactive monomer, a thermosetting resin, an inhibitor, a conductive filler and a thixotropic agent; in, The reactive monomer comprises at least one of triethoxytrimethylolpropane triacrylate, pentaethoxytrimethylolpropane triacrylate, 1,6-hexanediol diacrylate, isobornyl acrylate or tripropylene glycol diacrylate, the thermosetting resin comprises polyurethane acrylate or amine acrylate, and the inhibitor comprises 4-tert-butylcatechol or tallow diamine dioleate.
2. The anti-oxidation conductive heat dissipation copper paste adhesive as claimed in claim 1 comprises 3-17wt% of reactive monomer, 5-15wt% of thermosetting resin, 0.5-4wt% of polymerization inhibitor, 75-90wt% of conductive filler and 0.1-3wt% of thixotropic agent.
3. The anti-oxidation conductive heat dissipation copper paste adhesive according to claim 1 or 2, wherein: The conductive filler is conductive copper powder.
4. The anti-oxidation conductive heat dissipation copper paste adhesive according to claim 3, wherein: The median particle size of the conductive copper powder is between 0.1 μm and 10 μm, and the ratio of D90 / D50 of the particle size of the conductive copper powder is less than 3.
5. The anti-oxidation conductive heat dissipation copper paste adhesive according to claim 1, wherein: The thixotropic agent comprises polyamide wax or oxidized polyethylene wax.
6. A method for preparing an anti-oxidation conductive heat dissipation copper paste adhesive, comprising: Step 1: uniformly mix a reactive monomer, a thermosetting resin and a polymerization inhibitor to obtain a first mixed copolymer, wherein: The reactive monomer comprises at least one of triethoxy trimethylol propane triacrylate, pentaethoxy trimethylol propane triacrylate, 1,6-hexanediol diacrylate, isobornyl acrylate or tripropylene glycol diacrylate, wherein the thermosetting resin comprises polyurethane acrylate or amine acrylate, and wherein the polymerization inhibitor comprises 4-tert-butylcatechol or tallow diamine dioleate; Step 2: adding a conductive filler into the first mixed copolymer and mixing them evenly to obtain a second mixed copolymer; and Step 3: Add a thixotropic agent into the second mixed copolymer and mix them evenly to obtain the anti-oxidation conductive heat dissipation copper paste adhesive.
7. The preparation method according to claim 6, wherein The conductive filler is conductive copper powder.
8. The preparation method according to claim 7, wherein The median particle size of the conductive copper powder is between 0.1 μm and 10 μm, and the ratio of D90 / D50 of the particle size of the conductive copper powder is less than 3.
9. The preparation method according to claim 6, wherein: The thixotropic agent comprises polyamide wax or oxidized polyethylene wax.
10. A use of the antioxidant conductive heat dissipation copper paste adhesive according to any one of claims 1 to 5 for fixing semiconductor components, wherein the antioxidant conductive heat dissipation copper paste adhesive comprises 3-17wt% of reactive monomers, 5-15wt% of thermosetting resins, 0.5-4wt% of polymerization inhibitors, 75-90wt% of conductive fillers and 0.1-3wt% of thixotropic agents.
